Analysis of Internal and External Factors On Asset Growth at PT. BPRS Aceh Province (International Journal of Scientific Research and Management (IJSRM), 2024)
Currently, the development of BPRS from year to year has increased. This increase can be seen through the BPRS total asset report. Many factors influence the growth of total assets of Islamic banks, including internal and external factors. This research aims to determine the effect of inflation, DPK and NPF on the growth of Total Assets in BPRS Aceh Province. The method used in this research is a quantitative method. The sampling technique used was purposive sampling, so that 11 companies were obtained as samples. The data used in this research is panel data. The data in this research comes from financial reports obtained from BPRS Banks in Aceh Province. The data analysis technique uses multiple linear regression analysis, previously carried out a classical assumption test. The results of the F test show that inflation, DPK and NPF together (simultaneously) have an effect on total assets at PT Bank BPRS. The results of the t test show that inflation partially influences total assets at PT Bank BPRS, DPK partially influences total assets at PT Bank BPRS, NPF partially influences total assets at PT Bank BPRS.